Identification of Echinodermata in Drieng Leupung Beach As Zoology Invertebrata Learning Media - Jalaluddin Jalaluddin; Jumarsa Jumarsa; Ariaty Ariaty; Azwir Azwir; Dina Ariani (International Conference on Multidisciplinary Research, 2021)
Echinoderms are marine animals which include sea cucumbers and starfish phylum. These animals can be found in almost every level of sea zonal depth; from the intertidal zone to the abyssal zone. This phylum contains about 7000 living species, making it the second-largest group after chordates. This study aims to determine the types of Echinoderms found in Drieng Leupung Beach. The parameters used were the types of Echinoderms found in Drieng Leupung Beach. The research was conducted using the line transect method with purposive sampling technique. The data were presented descriptively, and the results show that the beach location is home for 4 classes of Echinoderms; 8 species of Asteroidea class, 5 species of Holothuroidea class, 4 species from Echinoidea class, and 1 species from Ophiuroidea class, with a total of 17 species found.  Species of Crinoidea class was not found. The most common type of species found is from the Echinoidea class, namely Diadema Setosum. This is due to the environmental factors that are very supportive for the species to grow. One of which is the temperature factor, which is around 26o C-28o C, which is an ideal temperature for Diadema Setosum to breed. The availability of food is another influential factor.   Keywords: Identification, Echinodermata (Echinoderms), Drieng Beach